Avenues for post-translational protein modification prevention and therapy. (August 2022) - Tang, Mengyao; Kalim, Sahir
Abstract: Non-enzymatic post-translational modifications (nPTMs) of proteins have emerged as novel risk factors for the genesis and progression of various diseases. We now have a variety of experimental and established therapeutic strategies to target harmful nPTMs and potentially improve clinical outcomes. Protein carbamylation and glycation are two common and representative nPTMs that have gained considerable attention lately as favorable therapeutic targets with emerging clinical evidence. Protein carbamylation is associated with the occurrence of cardiovascular disease (CVD) and mortality in patients with chronic kidney disease (CKD); and advanced glycation end products (AGEs), a heterogeneous group of molecules produced in a series of glycation reactions, have been linked to various diabetic complications. Therefore, reducing the burden of protein carbamylation and AGEs is an appealing and promising therapeutic approach. This review chapter summarizes potential anti-nPTM therapy options in CKD, CVD, and diabetes along with clinical implications. Using two prime examples—protein carbamylation and AGEs—we discuss the varied preventative and therapeutic options to mitigate these pathologic nPTMs in detail. We provide in-depth case studies on carbamylation in the setting of kidney disease and AGEs in metabolic disorders, with an emphasis on the relevance to reducing adverse clinical outcomes such as CKD progression, cardiovascular events, and mortality. Overall, whether specific efforts to lower carbamylation and AGE burden will yield definitive clinical improvement in humans remains largely to be seen. However, the scientific rationale for such pursuits is demonstrated herein.